Get ’Er Done: Experiences of Canadian Farmers Living with Chronic Low Back Disorders - Bath, Brenna (Physiother Can, 2019)
Purpose: This study explored the experiences of adult farmers living with chronic low back disorders (LBDs) in Saskatchewan. Method: A qualitative phenomenological approach with inductive thematic analysis was used to analyze semi-structured interviews that had been audio recorded and transcribed verbatim. Interview items focused on the perceived cause of LBDs, their impact on social and work life, coping strategies, and health care access and use. Results: A total of 12 face-to-face interviews were conducted with 11 men and 1 woman aged 40–84 years. Two overarching themes emerged: seasonality and isolation. Related sub-themes included pushing through, doing less, barriers to health care, and self-management. Conclusions: Farmers are faced with seasonal demands and geographical constraints, which lead them to push through the pain or do less when experiencing an episode of low back pain. In addition, farmers identified many barriers to accessing health care services that caused them to develop self-management techniques to cope or to go without care. This study provides the groundwork for future research addressing the unique occupational demands of farmers. Knowledge of farmers’ experiences with chronic LBDs and their challenges regarding health care access can help inform health care providers and decision makers and contribute to tailored services and management approaches for similar rural and remote regions in other parts of the world.